IMPLEMENTASI KEBIJAKAN PERCEPATAN POPULASI TERNAK DI KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR TAHUN 2017 - Sukmana, Sapta; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The main essence of policy implementation is understanding what should happen after a program is declared valid or formulated. This understanding includes efforts to administer it and have a real impact on the community or events. Then the implementation of the policy can be interpreted as the implementation of activities or activities referring to the guidelines that have been implemented can have an impact or impact on the community and can contribute in overcoming the problems that are targeted by the program.               This study aims to understand the Implementation of Policy for the Acceleration of Cattle and Buffalo Populations in Bagan Sinembah Subdistrict, Rokan Hilir Regency in 2017. Theoretical Framework uses Policy Implementation According to Merrile S. Grindle, namely Policy Content and Policy Context. This research was conducted in Bagan Sinembah District, Rokan Hiir Regency. Data collection techniques are done by interview and documentation. The method used in this research is descriptive qualitative.               The results of this study indicate that in its implementation in the Rokan Hilir Regency precisely in the Bagan Sinembah District has not been going well. Because cow self-sufficiency has only been running for 1 to 2 years so there is no evaluation from the government what are the factors that hamper this self-sufficiency in cattle. Rokan Hilir Regency still lacks Human resources, namely lack of veterinarians. With a livestock population in Rokan Hilir, around 20,000, the Rokan Hilir District has only 7 veterinarians, which is not yet commensurate with the livestock population. Government institutions that function as coaches, supervisors, researchers and implementers of education, training and counseling have not functioned properly in managing the institutional breeders for thedevelopment of the cattle self-sufficiency. Keywords: Implementation, Policy, Population